Effect of mushroom chitosan coating on the quality and storability of tomato (Solanum lycopersicum L.) - B, Meenu; Raman, Maya; P U, Sreelekshmi; Mathew , P T (Journal of Postharvest Technology, 2023)
Tomato is known for its high nutritional content and commercial importance. It is also known for its high productivity and easy manipulation. Nevertheless, the postharvest losses faced by tomato industry is enormous that can be attributed to the inappropriate preservation and packaging techniques. The application of biodegradable films and coatings could be a promising alternate preservation method. It provides a protective layer and creates a modified atmosphere in the fruit. The effects of fungal (Pleurotus ostreatus) chitosan coating on the quality attributes and delayed ripening of tomato (Lycopersicon esculentum) were investigated. The fruits were treated with 0.5, 1.0 and 2.0% chitosan solution and were stored at at room temperature (32±1°C, 75-80% relative humidity). The mushroom chitosan extracted and characterized; and compared with shrimp shell chitosan. Results showed that the ripening of tomato were significantly delayed by the treatment of chitosan coating in a concentration-dependent manner. The 2.0% chitosan coating was the most effective. The loss of firmness and color change was efficiently inhibited by 1.0% chitosan coating during storage. The decline in titratable acidity and fruit weight were effectively inhibited by the chitosan coating. These results suggested that the application of mushroom chitosan coating may exhibit potential for delaying ripening of tomato during storage in practice, thereby considerably reducing the postharvest losses.